Hidden in plain sight : an archaeology of magic and the cinema - Williamson, Colin, 1984- (Techniques of the moving image., 2015)
What does it mean to describe cinematic effects as "movie magic," or to say that the cinema is all a "trick"? To answer these questions, Colin Williamson situates the cinema within a long tradition of magical practices and devices of wonder that combine art and science, involve deception and discovery, and evoke both awe and curiosity. Hidden in Plain Sight shows how, even as they mystify audiences, cinematic illusions also encourage them to learn more about the technologies and techniques behind moving images.